The Greater Transformation: Digitalization and the Transformative Power of Distributive Forces in Digital Capitalism - Pfeiffer, Sabine (International Critical Thought, 2021)
This article discusses digitalization and its connection with the political economy of transformation. Its point of departure is Karl Polanyi's historical analysis as presented in The Great Transformation. Polanyi analyzed the development of “self-regulating” markets—with transformative and destructive consequences for individuals, nature, and society—and government efforts to contain these consequences. Polanyi's perspective is compared to Marx's theorem of the development of productive forces. Their respective focal points are different but complementary. For Polanyi, the decisive historical and theoretical break (and the cause of the destructive effects) lies in the act of purchasing human labor, whereas for Marx it lies in the act of producing value and in the relations of production as well as the relations of distribution linked to it. Working from this theoretical basis, current developments in digitalization are analyzed not as a further development within productive forces but as a transforming development of distributive forces. Following the logic of The Great Transformation, current developments should thus not be interpreted as a second great transformation but as the augmentation of the first, leading to a “greater” transformation associated with even more destructive potential. This leaves little hope for a smooth transition into any form of post-growth society.
Sociology
Keywords: digital capitalism; digital transformation; distribution; political economy; productive forces

MERCADOS E PRAÇAS DE MERCADO: KARL POLANYI E O CAPITALISMO CONTEMPORÂNEO - Parpet, Marie France Garcia (Sociologia & Antropologia, 2021)
Resumo Explorando as distinções conceituais entre mercado, sistema de mercados formadores de preço e praça de mercado, concebidas por Karl Polanyi, o artigo mostra a pertinência dessas diferenças para a análise do capitalismo contemporâneo, ao focalizar a caracterização e os efeitos específicos de praças de mercado da atualidade. Evoca a contribuição de Polanyi para repensar o conceito de mercado tal como referido na literatura econômica e especificar a historicidade dos mercados, sobretudo do sistema de mercados formadores de preço (equivalente de sistema capitalista), opondo esses conceitos a praças de mercado. Recorre a trabalhos etnográficos e/ou sociológicos, sobre praças de mercado contemporâneas, verificando que elas existem nas configurações atuais das trocas mercantis e podem criar valor simbólico e material, estando na origem de processos de diferenciação social, intensificados, por exemplo, no caso das plataformas digitais.
Sociology; Anthropology
Keywords: Karl Polanyi; Mercado; institucionalização; plataformas digitais.; praça de mercado; salões de exposição; sistema de mercados

CAPITALISM, DEMOCRACY, AND SOCIAL THEORY IN KARL POLANYI: AN INTERVIEW WITH GARETH DALE - Santos, Rodrigo Salles Pereira dos; Onto, Gustavo Gomes (Sociologia & Antropologia, 2021)
Resumo Uma introdução à entrevista realizada com Gareth Dale (Brunel University) − economista político e especialista na trajetória e na obra de Karl Polanyi − e a um conjunto de textos inspirados na abordagem polanyiana publicados neste número de S&A. Recupera questões-chave apresentadas na entrevista e na obra de Dale, dando relevo à literatura recente produzida sobre o autor, à contínua e difundida relevância das ideias de Polanyi para a compreensão do capitalismo e da democracia, e a uma leitura crítica e aberta de suas contribuições teóricas. Divulga as contribuições específicas, teóricas e empíricas, de quatro artigos originais que mobilizam ativamente conceitos polanyianos no entendimento da pluralidade dos processos de enraizamento e das dinâmicas do movimento duplo, de mercantilização da terra e do trabalho, e da centralidade da praça de mercado no capitalismo contemporâneo; além dos aportes de um registro de pesquisa e duas resenhas sobre agências e pedagogias econômicas e financeirização da vida cotidiana. An introduction to the interview with Gareth Dale (Brunel University) − a political economist and expert on Karl Polanyi’s life and work − and to a set of papers, inspired by the Polanyian approach, published in the current issue of S&A. The paper highlights key questions presented in the interview and in Dale’s work, with a focus on the recent literature produced about the author, the continuous and widespread relevance of Polanyi’s ideas for the understanding of capitalism and democracy, and a critical and open reading of his theoretical contributions. Next, the paper presents the specific contributions, both theoretical and empirical, of four original papers that actively dip into Polanyian concepts in understanding the plurality of the embeddedness processes and the dynamics of the double movement, the commodification of land and labor, and the centrality of the marketplace in contemporary capitalism; as well as the contributions of a research recording and of two book reviews on economic agencies and pedagogies and the financialization of everyday life.
Sociology; Anthropology
Keywords: DALE; Gareth; Karl Polanyi; capitalism; democracy; market

The unfinished development of the frontier: a Karl Polanyi reading of the conflict between the forestry industry, Mapuche communities and the Chilean State - Undurraga, Tomás; Márquez, Felipe (Sociologia & Antropologia, 2021)
Resumo O artigo explora conflitos entre a indústria florestal, as comunidades Mapuche e o Estado chileno à luz da leitura de Polanyi sobre a expansão capitalista. Oferece análise histórico-institucional das maneiras pelas quais o Estado chileno usou a florestação para domar uma fronteira selvagem e os povos nativos que ali vivem. Argumenta que o aumento da violência nessa zona responde à crescente militarização do Estado na área e reflete o contramovimento de proteção social iniciado pelo povo Mapuche - contra uma indústria florestal de livre mercado que transformou a paisagem, limitando o acesso dos Mapuche a terras e florestas, e contra um processo de modernização liderado pelo Estado chileno que corroeu as instituições tradicionais dos Mapuche e lhes ofereceu integração em termos desiguais, como “campesinos pobres”.
Anthropology; Sociology
Keywords: Chile; Estado chileno; Mapuche; Polanyi; contramovimento; countermovement; forest industry; indústria florestal; proteção social; social protection

On the meaning and contemporary significance of fascism in the writings of Karl Polanyi - Millett, Kris (Theory and Society, 2021)
This paper assesses the contribution of Karl Polanyi, a theorist largely ignored in fascism scholarship, toward understanding fascism’s interwar rise and present-day implications. In exploring Polanyi’s work in The Great Transformation and lesser-known and unpublished writings, a sophisticated and largely original conception of fascism emerges, rooted in the idea of ‘anti-individualism’ as its foundational trait. Polanyi accounts for fascism’s philosophical content, ideological plasticity, political function and societal form, intervening in debates over how to define fascism, its ambiguity with the populist far-right, and on its both economically reactionary and socially revolutionary qualities. Polanyi’s analysis suggests an enduring vulnerability on the part of liberal capitalism to fascist currents as (1) a solution to the instability of the market economy (and broader incompatibility between capitalism and democracy) at the systemic level, and (2) to the crisis of the individual subject on a social and moral level. I end by considering how Polanyi’s theory might be applied to locate current neo-fascist movements and elucidate the sociological problems underpinning their existence.
Sociology
Keywords: Anti-individualism; Fascism; Neo-fascism; Polanyi; Totalitarianism; Vitalism

Karl Polanyi: a theorist of mixed economies - Szelényi, Iván; Mihályi, Péter (Theory and Society, 2021)
Karl Polanyi’s scholarship is interpreted in radically different ways. The “hard” reading of Polanyi sees him as a radical socialist; the “soft” reading presents him as a theorist of mixed economy. This article sides with the soft interpretation. It uses Polanyi’s biography to explain his theoretical “elusiveness,” presents a novel interpretation of his three types of economic integration, claiming all economies are “mixed.” While it acknowledges Polanyi as one of the major sources of world system theory, it claims that Polanyi saw not only the dangers, but also the necessity and positive consequences of globalization. Finally, it shows that, in spite of Polanyi’s life-long commitment to the political left, his scholarly work did not offer an apology of socialism. Instead this article uses Polanyi’s theory of economic integration to build a critical political economy of state socialism.
Keywords: capitalism; reciprocity; redistribution; rent-seeking; socialism; world system theory

Going public with Polanyi in the era of Trump * - Burawoy, Michael (The Routledge International Handbook of Public Sociology, 2021)
After considering different possible elements of the ‘Trump era,’ I will turn to The Great Transformation to periodize capitalism into three waves of marketization and their counter-movements. In the first wave, we follow the commodification of land, money and especially labor, so-called fictitious commodities, and the local counter-movements marketization inspired, reaching to the level of the state. In the second wave, the focus turns on the way marketization generated a reaction from states, seeking to regulate commodification – in other words, processes of de-commodification. Given the tension between capitalism and democracy, in Polanyi’s view essentially two forms of regulation were possible: either democracy suppresses capitalism and we get socialism, or capitalism suppresses democracy and we get fascism. He neither paid much attention to the popular forces that led in either direction nor to the possibility of a compromise between capitalism and democracy that reigned in three decades after World War Two. Beginning in the 1970s, we witnessed the beginning of a third wave of marketization – more commonly known as neoliberalism – that Polanyi did not anticipate. I attribute his failure to anticipate another wave of marketization to the contradictory pressures of accumulation that are temporarily alleviated by commodification. In this third wave, I show how democracy is discredited, and consensus politics dissolves into polarizing movements within and beyond parliamentary politics. The lived experience driving these movements, I argue, revolves around processes of re-commodification and ex-commodification of nature, money, labor and knowledge. This is the terrain upon which sociology must engage its publics. I highlight two approaches, both founded on an organic public sociology that engages directly with publics. On the one hand, there is the empathic public sociology that wades into communities in order to comprehend the distinctive ‘deep narrative’ of right wing populism, typified by Arlie Hochschild’s Strangers in Their Own Land. On the other hand, there is the affirmative public sociology that creates a collective vision based on a dialogue with the practitioners of real utopias, typified by Erik Wright’s How to Be an Anti-Capitalist in the Twenty-First Century.
Sociology
Keywords: Trumpism; marketization; public sociology

Karl Polanyi: The Great Transformation - Ebner, Alexander (Schlüsselwerke der Wirtschaftssoziologie, 2021)
Karl Polanyi war in jungen Jahren Zeitzeuge der vielschichtigen ökonomischen, sozialen und politischen Umwälzungen in der österreichisch-ungarischen Donaumonarchie. 1886 in Wien geboren, wuchs er in Budapest auf, wo er Rechtswissenschaft und Philosophie studierte, um dann nach der Zerschlagung der ungarischen Räterepublik nach Wien zurückzukehren. Dort schrieb er für die wirtschaftspolitische Wochenzeitschrift „Österreichischer Volkswirt“.
Keywords: biography

Instituições Sociais e Sistema Econômico: a perspectiva de Karl Polanyi - Freitas, Tales Rabelo (Revista da Sociedade Brasileira de Economia Política, 2021)
For Karl Polanyi, the economic system cannot be analyzed in isolation from social institutions. The economicism fallacy neglects social variables that are fundamental for determining economic action and systemic transformations. This implies that the rise of the self-regulated market system and its dominance over social institutions are not a natural movement when analyzed in the light of the entire history of human societies. For the author, what happened was a kind of uprooting of the economy, although this movement has been supported in a very specific institutional context in the past, and with no possibility of sustainability. As the economy is a by-product of social institutions, the Polanyian approach understands that any analysis, whether of economic dynamics or its transformations, must be carried out taking into account the needs of society as a whole.
Sociology; Political Science
Keywords: Karl Polanyi; economicismo; economism; instituições; institutions

Fascism and the enduring problem of the liberal individual in Polanyi - Millett, Kris (Dewey Studies, 2021)
This application of Polanyi to the question of fascism’s resurgence provides an important corrective to mainstream liberal explanations (e.g., Albright 2018), inviting the reader to “look up rather than down” (Lim 2021) by tying fascism’s significance to the functioning of the capitalist system rather than to the personalities of fascist politicians or their degree of mass support. The merits of this notwithstanding, I argue that current Polanyian treatments have neglected to engage with a core aspect of Polanyi’s theory, which is that fascism, at its roots, is a fundamentally anti-individualist ideology that aims to address a moral and social crisis of the individual subject in liberal capitalism. Omitting this risks obfuscating what makes fascism distinctive as well as why its ideas have retained their appeal.
Sociology
Keywords: essence of fascism; fascism; individualism